Gender Imbalance in New Zealand's Senior Legal Positions - Guy-Meakin, Amelia (Victoria University of Wellington Law Review, 2014)
Despite New Zealand's real progress toward gender equality over the past century, women remain under-represented in the country's senior legal positions. Disparities between men and women are not unique to the legal profession. They are particularly problematic, however, given that the law aims to pursue justice, and equal opportunity should be its paramount concern. This article examines some of the obstacles and constraints women face in attaining leadership roles in the New Zealand legal profession. Preliminary solutions to remedy these obstacles and constraints are proposed, including a necessary recognition that many female professionals offer distinct experiences and have different needs to their male counterparts.